The reference air kerma rate comparison between measurements and certificates for Ir-192 high dose rate - จำปางิน โชติกา; วรรณวิจิตร ชุลี; กิ่งแก้ว ศักดา (Journal of Thai Association of Radiation Oncology, 2018)
Background: Brachytherapy patients should be obtained accurate dose in order to treat as intended. Objective: To report retrospective comparison of measured reference air kerma rate (RAKR) for Ir-192 HDR(high dose rate) pellet source with the certificate issued by the manufacturer. Materials and methods: The well-type ionization chamber was a measurement tool of 22 RAKR for Ir-192 pellet sources MicroSelectron V2 type. It was connected to the electrometer to read collected charge. The pellet dwell position that presented the maximum reading of collected charge value was searched. The collected charge reading at maximum reading dwell position was performed for 3 times for each 300 seconds dwell time. The averaged charge readings were corrected for source transit effect calibrated, air density and charge recombination. The reading was calculated to RAKR and compared with the manufacturer’s one. Results: The maximum charge reading position was found at 19th pellet dwell position. The RAKR differences between measurement and certification were ranged from -0.76% to+1.15% with the average value of -0.02±0.56%. The measured RAKRs were less than the certificate done for 12 out of 22 pellets. The differences between measured and manufacturer’s RAKRs were larger than 1% noticed for 2 out of 22 pellets. Conclusion: Each replacement of the new source, the medical physicist must verify the manufacturer’s RAKR. It is an important process as the quality control in brachytherapy treatment. This study shows that the differences between measured RAKR and the certificate are in the range from -0.76% to +1.15% which is not more than ±3% as required by universal standard.